Perceived risk and debt behaviour in the stock market: A survey of investors in Vietnam - Phung Trang M. T.; Wei Huei Hsu; Michael J. Naylor; Martin R. Young (Cogent Economics & Finance, 2022)
While informal debt is often used as a funding source for retail investors, very little is known about the characteristics of its sources and use. This is particularly true in emerging markets where the use of informal debt is widespread. We examine the determinants of the use of informal debt of individual investors in the Vietnam stock market and find that perceived risk has a positive impact on informal debt decisions, that borrowing sources are primarily from parents and friends and that experience, wealth and borrowing sources have a positive impact. We also find that women perceive higher risks in stock investments than men do.The policy implication is that informal debt sources play a significant part in stock market development, and therefore, a greater level of attention needs to be paid to them. Policies need to be developed that increase and manage informal sources of investment finance.
Keywords: 330; informal debt; informal sources; perceived risk; stock investment